PENGARUH FAKTOR TEKNOLOGI, KUALITAS PRODUK DAN FOKUS PADA PELANGGAN TERHADAP KEPUASAN PELANGGAN (STUDI PADA RESTORAN SAUNG DAPOER KAMPOENG) - Arther Evert Samuel; Kholid Farid (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2017)
The purpose of this research was determined to know the influence of factor of technology, product quality, and focus on customer toward customer satisfaction at Saung Dapoer Kampoeng Restaurant. The population of this research was all people who came and made a purchase in Saung Dapoer Kampoeng Restaurant and to set the sample of research used non-probability sampling method by combining convenience and purposive sampling techniques on as many as 85 respondents. The results of data quality test showed that the instruments of this research are valid and reliable and fulfill the requirements of classical assumption analysis. The results of multiple linear regression analysis showed that the predictor of focus on customer had the most dominant effect on customer satisfaction, afterwards product quality predictor, and the last one was predictor of factors of technology contributed the smallest influence toward customer satisfaction.